Comparative analysis of IMP-4- and OXA-58-containing plasmids of three carbapenemase-producing Acinetobacter ursingii strains in the Netherlands. (December 2022) - Hendrickx, Antoni P.A.; Schade, Rogier P.; Landman, Fabian; Bosch, Thijs; Schouls, Leo M.; van Dijk, Karin
Highlights: Three Acinetobacter ursingii strains harbor IMP-4 and OXA-58. IMP-4 and OXA-58 were co-localized on different multi-resistance plasmids. IMP-4/OXA-58 plasmids partially resembled an Acinetobacter johnsonii plasmid. johnsonii may represent a source of carbapenem resistance genes for A. ursingii . Abstract: Objectives: A recent occurrence of carbapenemase-producing Acinetobacter ursingii was reported in the Netherlands and comprised three unrelated strains carrying the bla IMP-4 and bla OXA-58 encoding genes. The objective was to investigate a putative common source of the carbapenemase resistance genes and plasmids in these A. ursingii strains. Methods: Hybrid assembly of short-read and long-read sequencing data was performed using Unicycler and assembled genomes were analysed by ResFinder and PlasmidFinder. Results: Hybrid assemblies of A. ursingii genomes yielded a circular chromosome, a large plasmid harboring bla IMP-4 and bla OXA-58 genes (sizes 259–317kb), and four to five other smaller plasmids. ResFinder analyses revealed 16 other acquired resistance genes on the plasmids carrying the bla IMP-4 and bla OXA-58 genes. These 18 genes encode resistance towards eight antibiotic classes. The smaller plasmids did not carry acquired resistance genes. Comparative analysis showed that the three bla IMP-4 / bla OXA-58 plasmids were similar (61%–83%) and shared 13 to 17 of the 18 resistance genes. BLAST analysis showed that the bla IMP-4 / bla OXA-58 plasmids were not reported before. However, a close match with a 399 kb plasmid from Acinetobacter johnsonii was found (99% similarity, 80% coverage). This A. johnsonii plasmid contains the bla OXA-58 gene, but lacks bla IMP-4, and it shares eight other resistance genes with those present on the A. ursingii bla IMP-4 / bla OXA-58 plasmids. Conclusion: Three bla IMP-4 / bla OXA-58 -carrying plasmids were characterized in three carbapenemase-producing A. ursingii strains. The plasmids were highly similar, suggesting a putative common source or co-selection of resistance genes from A. johnsonii . These results provide initial insights in the dissemination of carbapenem-resistance in A. ursingii in the Netherlands.